Epidemiological analysis of meningitis cases in children in Brazil from 2010 to 2020 (Research, Society and Development, 2022)
Meningitis is a disease with a high fatality rate, requiring timely and appropriate diagnosis and treatment to avoid death and sequel. This disease can lead to lifelong disability for survivors. In this context, the objective of this research was to evaluate the epidemiological profile of meningitis cases in Brazil, diagnosed in children younger than 1 year and up to 9 years and 11 months, in the period from 2010 to 2020. The present research was carried out through a retrospective, quantitative study, with temporal secondary data collected from the DATASUS database according to the Notifiable Diseases Information System (SINAN). The variables evaluated were: age group, region of notification, sex, race, etiology and diagnostic method. Data were analyzed using descriptive statistics and were represented in the form of graphs. In Brazil between 2010 and 2020, 187,508 cases of meningitis were diagnosed, of which 87,939 corresponded to children under one year and up to 9 years and 11 months and 28,384 cases in children under 1 year. The Southeast region had the highest number of children and neonates with meningitis, and the lowest number in the North region. Viral meningitis prevailed over bacterial. Males and white and brown races were the most affected by the disease. The diagnostic criteria were: chemocytological, clinical, culture, PCR-viral, AG Latex, clinical-epidemiological and bacterioscopy.